P-I class metalloproteinase from Bothrops moojeni venom is a post-proline cleaving peptidase with kininogenase activity: Insights into substrate selectivity and kinetic behavior - Okamoto, Debora N.; Kondo, Marcia Y.; Oliveira, Lilian C. G.; Honorato, Rodrigo V.; Zanphorlin, Leticia M.; Coronado, Monika A. [UNESP]; Araujo, Mariana S.; Motta, Guacyara da; Veronez, Camila L.; Andrade, Sheila S.; Oliveira, Paulo S. L.; Arni, Raghuvir K. [UNESP]; et al. (Elsevier B.V., 2014)
Snake venom metalloproteinases (SVMPs) belonging to P-I class are able to hydrolyze extracellular matrix proteins and coagulation factors triggering local and systemic reactions by multiple molecular mechanisms that are not fully understood. BmooMP alpha-I, a P-I class SMVP from Bothrops moojeni venom, was active upon neuro- and vaso-active peptides including angiotensin I, bradykinin, neurotensin, oxytocin and substance P. Interestingly, BmooMPa-I showed a strong bias towards hydrolysis after proline residues, which is unusual for most of characterized peptidases. Moreover, the enzyme showed kininogenase activity similar to that observed in plasma and cells by kallikrein. FRET peptide assays indicated a relative promiscuity at its S-2-S '(2) subsites, with proline determining the scissile bond. This unusual post-proline cleaving activity was confirmed by the efficient hydrolysis of the synthetic combinatorial library MCA-GXXPXXQ-EDDnp, described as resistant for canonical peptidases, only after Pro residues. Structural analysis of the tripeptide LPL complexed with BmooMP alpha-I, generated by molecular dynamics simulations, assisted in defining the subsites and provided the structural basis for subsite preferences such as the restriction of basic residues at the S-2 subsite due to repulsive electrostatic effects and the steric impediment for large aliphatic or aromatic side chains at the Si subsite. These new functional and structural findings provided a further understanding of the molecular mechanisms governing the physiological effects of this important class of enzymes in envenomation process. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Snake venom metalloproteinase; Kininogenase activity; FRET peptides; Substrate specificity; Molecular dynamics simulations